ANALYSIS OF THE RELATIONSHIP BETWEEN FEED VEGETATION CHARACTERISTICS IN FOREST GAPS WITH EATING ACTIVITIES OF JAVAN RHINO (Rhinoceros sondaicus Desmarest, 1882) IN UJUNG KULON NATIONAL PARK: RESORT CIBANDAWOH AND CIKEUSIK - Azmi (NIM : 11513047), Muhammad
Abstract - Javan rhinoceros (Rhinoceros sondaicus Desmarest, 1882 ) are a species with a threathened population in Indonesia limited to Ujung Kulon National Park. Javan rhinos are known to require many types of feed for survive. Forest gaps are reported as the most favored habitat for the Javan rhinos eating activities. This study aims to analyze the relationship between the characterstics of rumpang represented by its richness of feed species, diversity of feed species, evenness of feed type, pattern of distribution of feed type and prefered feed types with the Javan rhinos feeding activity in four different types rumpang in Cibandawoh (CBDW 01 dan CBDW 02) and Cikeusik (CKSK 01 dan CKSK 02). Vegetation analysis are carried out with a squared plot method, where Javan rhino feed was type and number of individuals were recorded. Preference of gap and feed type preference is measured by the Neu Preference Index. Characteristics of the vegetative structure is measured with Margalef Index (Dmg), Shannon – wienner Index (H’), Pielou Index (J’) and pattern of feed distribution measured with the Morisita Index. The results obtained from this study shows that the Javan rhino prefer gaps CBDW 02 (3,16) and CKSK 02 (2,22). Factors influencing the preference of gaps ari the clumped distribution pattern in CBDW 02 92% (23 species) and CKSK 02 88% (22 species) and the proportion of prefered feed type CBDW 02 24% (6 type) and CKSK 02 16% (4 type). It can be concluded that the presence of Javan rhinos in a gap is influenced by the distribution pattern of feed types and the proportion of prefered feed types.